The globalization of human rights - Coicaud, Jean-Marc; Doyle, Michael, 1948-; Gardner, Anne-Marie (United Nations system in the 21st century., 2003)
This work focuses on the imperatives of justice at the national, regional, and international levels through an analysis of civil, political, economic, and social rights.